Idiopathic pulmonary fibrosis in a patient with rheumatoid arthritis - D.V. Dobrianskyi; N.A. Tahiieva; M.S. Khranovska; K.V. Mazurenko; P.F. Dudka; I.P. Tarchenko; А.О. Dorokhova (Infusion & Chemotherapy)
ABSTRACT. The purpose of this paper is to draw the attention of practicing physicians to the importance of timely treatment and difficulties in managing patients with idiopathic pulmonary fibrosis (IPF), especially in cases of combination with other chronic diseases, in particular rheumatoid arthritis. The paper describes a clinical case of IPF, which due to its gradual progressive course was not perceived by the patient as a clinically important disease. A feature of the course of IPF in this patient was the discovery of numerous widespread bronchiectasis with bullae up to 7.5 cm in diameter, a complication was their infection with a multidrug-resistant strain of Acinetobacter baumannii, which made further effective treatment impossible. The patient was referred for inpatient treatment due to the existing active respiratory tract infection, which was accompanied by severe intoxication, shortness of breath, cough and general weakness. Despite the combination therapy, the patient's condition progressively worsened. Subsequently, the patient developed a septic state and multiple organ failure. The patient died on the 33rd day of hospitalization. This case demonstrates the complexity of managing patients with comorbid pathology and existing IPF, emphasizes the importance of early diagnosis and the availability of affordable antifibrotic therapy, as well as timely monitoring of disease progression and infectious complications.